2020
DOI: 10.3390/su12166603
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Soil Moisture and Evaporation under the Activities of Earthworms in Typical Anthrosols in China

Abstract: Earthworms have an important influence on the terrestrial ecological environment. This study assesses the effect of different earthworm densities on soil water content (SWC) and evaporation in a laboratory experiment. Four earthworm densities (0 no-earthworm, control [C]; 207 earthworms m−2, low density [LDE]; 345 earthworms m−2, medium density [MDE]; and 690 earthworms m−2, high density [HDE]) are tested in soil columns. Results show that cumulative evaporation occurs in the decreasing order of densities: C (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…Furthermore, they influence the soil aggregate formation by secreting a large amount of mucus (Scullion & Malik, 2000), which influences the soil physical and chemical properties (Spurgeon et al, 2013). Generally, large earthworms form large soil aggregates, whereas smaller earthworms destroy macroaggregates and excrete smaller aggregates (Blanchart et al, 1997; Blouin et al, 2013; Ma et al, 2020). The inoculation earthworms from South America significantly ( p < 0.05) promoted the formation of macroaggregates, while Eisenia foetida mainly promoted the formation of small aggregates ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, they influence the soil aggregate formation by secreting a large amount of mucus (Scullion & Malik, 2000), which influences the soil physical and chemical properties (Spurgeon et al, 2013). Generally, large earthworms form large soil aggregates, whereas smaller earthworms destroy macroaggregates and excrete smaller aggregates (Blanchart et al, 1997; Blouin et al, 2013; Ma et al, 2020). The inoculation earthworms from South America significantly ( p < 0.05) promoted the formation of macroaggregates, while Eisenia foetida mainly promoted the formation of small aggregates ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The grass-clover leys could improve earthworms numbers and soil quality within 1 year.Studies have shown that the ecological functions of earthworms are positively correlated with their biomass Miriam et al (2017). found that enzyme activity, microbial biomass and nutrients were increased through promotion of earthworms populations in the subsoil Ma et al (2020). suggested the quantity of earthworms population might provide valuable services in the soil micro-ecosystem.…”
mentioning
confidence: 95%
“…Minnich (1997) menyebutkan bahwa pada kelembaban yang terlalu tinggi atau terlalu banyak air, cacing tanah cenderung lebih sedikit dan berpindah ke bagian tanah dengan tempat pertukaran udara (aerasi) lebih baik. Lebih lanjut, Ma et al (2020) menyatakan bahwa cacing tanah juga berperan dalam memperbaiki kapasitas tanah memegang air, dan mengurangi evaporasi air tanah. Wu et al, (2017) Hal ini terjadi karena cacing tanah mengambil oksigen dari udara bebas untuk pernafasannya melalui kulit.…”
Section: Hubungan Organisme Tanah Terhadap Sifat Tanah Gambutunclassified
“…Estimation is based on empirical data collected that EWM can play a role in improving the quality of ASS through improving its the ability to retain water, provide nutrients for plants, improve soil structure and neutralize soil pH. This role is believed to occur because the EWM structure has spaces that are able to absorb and store water which helps it to maintain soil moisture [1,14,15]. With this role, EWM has the potential as an alternative agrobiotechnology product to improve the quality of ASS and add nutrients, especially to substitute and utilize NPK efficiently.…”
Section: Introductionmentioning
confidence: 99%